2021
DOI: 10.1128/aac.00071-21
|View full text |Cite
|
Sign up to set email alerts
|

Various Novel Colistin Resistance Mechanisms Interact To Facilitate Adaptation of Aeromonas hydrophila to Complex Colistin Environments

Abstract: Aeromonas hydrophila , a heterotrophic and Gram-negative bacterium, has attracted considerable attention owing to the increasing prevalence of reported infections. Colistin is a last-resort antibiotic that can treat life-threatening infections caused by multidrug-resistant gram-negative bacteria. However, the mechanisms underlying colistin resistance in A. hydrophila remain unclear. The present study reveals four novel colistin resistance mechanisms in A. hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…Interestingly, polymyxin-resistant bacterial pathogens exhibit mutations in the genes encoding PhoPQ, PmrAB, and the operons they regulate, leading to their constitutive expression and LPS modification. There are hundreds of mutations documented in different organisms responsible for LPS modification leading to polymyxin resistance (Huang et al 2020 ; Liu et al 2021 ; Olaitan et al 2014 ; Poirel et al 2017a ).…”
Section: Polymyxins: the Last-resort Antibioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, polymyxin-resistant bacterial pathogens exhibit mutations in the genes encoding PhoPQ, PmrAB, and the operons they regulate, leading to their constitutive expression and LPS modification. There are hundreds of mutations documented in different organisms responsible for LPS modification leading to polymyxin resistance (Huang et al 2020 ; Liu et al 2021 ; Olaitan et al 2014 ; Poirel et al 2017a ).…”
Section: Polymyxins: the Last-resort Antibioticsmentioning
confidence: 99%
“…However, with the indiscriminate use of polymyxins in aquaculture, resistance is increasingly being reported (Gonzalez-Avila et al 2021 ). In A. hydrophila , the primary way by which colistin resistance develops is by increased expression of the TCS EnvZ/OmpR that regulates the LPS modification pathway via the addition of L-Ara4N moiety to the lipid A (Liu et al 2021 ). It has also been observed that EnvZ/OmpR regulates the expression of an outer membrane protein (encoded by the gene 3832) which is predicted to be an autotransporter possibly involved in colistin uptake.…”
Section: Polymyxins: the Last-resort Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of gene 1038 was significantly increased in the colistin-resistant strain 23-C-23 compared to that of the colistin-susceptible strain WCX23 ( Fig. 1A ) via quantitative reverse transcription-PCR (RT-PCR) using the primers gene 1038 -F (5′- GCTGCTTCGGCTTCCTCTAT -3′) and gene 1038 -R (5′- GGTCTCGCCGAACATGAGAT -3′) as previously described ( 4 ). This suggests that gene 1038 might be associated with colistin resistance in A. hydrophila .…”
Section: Lettermentioning
confidence: 98%
“…This suggests that gene 1038 might be associated with colistin resistance in A. hydrophila . To test this hypothesis, gene 1038 was knocked out in a 23-C-23 background (23-C-23:Δgene 1038 ) and subsequently restored in complemented strain 23-C-23:CΔgene 1038 , as previously described ( 4 ) (see Table S1 in the supplemental material). The results showed that the colistin MIC for 23-C-23:Δgene 1038 was 8-fold lower than for the parent strain and that the complementation of gene 1038 in 23-C-23:CΔgene 1038 restored resistance to colistin ( Table 1 ).…”
Section: Lettermentioning
confidence: 99%